IMPLEMENTASI METODE WEIGHTED MOVING AVERAGE DAN SINGLE MOVING AVERAGE DALAM SISTEM INFORMASI PENJUALAN PADA KIOS MAUPA TORAJA UTARA - Kadang, Marsellus Oton; Patulak, Desi; Upa, Samrius (JTRISTE, 2022)
Forecasting the amount of sales of goods is one application of information technology in data mining. Forecasting aims to predict an event what will happen in the future. This study aims to design a system to predict the number of sales at the North Toraja Maupa Kiosk using 2 methods, namely the Weighted Moving Average (WMA) method and the Single Moving Average (SMA) method. Forecasting in research uses 7 samples of goods with 6 months of sales data. From the forecasting results using the 2 methods in question, the results of the Mean Average Percentage Error (MAPE) are obtained with forecasting values that are equally good with a percentage level for the WMA method of 17.1% and the SMA method of 15.71%.